The FOMC versus the Staff: Where Can Monetary Policymakers Add Value? - Romer, Christina D; Romer, David H (American Economic Review, 2008)
A key issue in monetary policymaking is the appropriate division of labor between the profes? sional staff of the central bank and the appointed policymakers. Lars E. O. Svensson (1999) argues that the appropriate role of a policymaking group, such as the Federal Open Market Com? mittee (FOMC) in the United States, is to make judgments about social welfare, taking as given the likely outcomes of different policies as esti? mated by the staff. In this division, the staff is relied upon to assess current and prospective economic conditions and to forecast the effects of different policies. Policymakers' only role is to decide which of the various options should be chosen.